Arabic Font Desigin Using Quadratic Bezier-Like Curve - Iman Aissa Alghannay Ahmed; Almbrok Hussin Alsonosi Omar; Jamaludin Md Ali (Journal of Pure & Applied Sciences, 2022)
This paper has constructed a linear quadratic Bézier-like curve with two shape parameters. The proposed work is to design the Arabic fonts by using Bezier-like curves. The focus of this study is to study the new functions of the Bezier-like curve and look at their application in designing Arabic fonts. Our new procedures involve a combination of quadratic and linear polynomial basis functions. The new functions of rational and non-rational Bezier-like curve are used to design Arabic fonts. The shape of the curve is modified as desired by simply altering the values of the shape parameters without changing the control polygon. The present study also looks at the extent of the approximation of the Arabic script design to its digitized image using the Bezier-like curves. The results of this study confirm that all generated functions can give the very visually pleasing shapes of the Arabic fonts similar to the original.